Explaining disproportionately high rates of adverse birth outcomes among African Americans the impact of stress, racism, and related factors in pregnancy. [article]. - Giscombe, C. L.
Compared with European Americans, African American infants experience disproportionately high rates of low birth weight and preterm delivery and are more than twice as likely to die during their 1st year of life. The authors examine 5 explanations for these differences in rates of adverse birth outcomes: (a) ethnic differences in health behaviors and socioeconomic status; (b) higher levels of stress in African American women; (c) greater susceptibility to stress in African Americans; (d) the impact of racism acting either as a contributor to stress or as a factor that exacerbates stress effects; and (e) ethnic differences in stress-related neuroendocrine, vascular, and immunological processes. The review of the literature indicates that each explanation has some merit, although none is sufficient to explain ethnic disparities in adverse birth outcomes. There is a lack of studies examining the impact of such factors jointly and interactively. Recommendations and cautions for future research are offered. -- (from the author)